A Way Out? Bird Metaphors in Psalm 102 - Siquans, Agnethe (Biblische Zeitschrift, 2026)
This article shows how the bird metaphors in Ps 102 create an alternative space for the troubled praying person. In V. 7-8, the praying person is compared to birds: to owls who are inhabitants of desert places and a small bird or sparrow who is described as lonely. V. 8 may suggest the situation of a sleepless night. On the one hand, these situations are by no means comforting and peaceful; on the other hand, the metaphors describe a place far away from the threatening enemies (V. 9). The bird metaphors are therefore ambiguous in this psalm. They create a spatial distance that separates the praying person from their social environment. This leads to loneliness and, at the same time, to safety from distress. As the praying self leaves their social place, which is no longer safe for them, a free space opens up.